Hubungan Pengetauan Siswa terhadap Ketaatan Perilaku Konsumsi Jajanan Sehat di SDN 03 Sumber Salak Ledokombo Jember - Febrika Devi Nanda; Hendrik Probo Sasongko (Vitamin : Jurnal ilmu Kesehatan Umum, 2024)
School children are susceptible to various snacks sold both at school and outside school. Lack of attention to the consumption of healthy snacks, resulting in the impact of decreased health, ranging from poisoning due to unhygienic storage and presentation processes to the risk of cancer due to the use of harmful food additives (Anak et al., 2019). This study aims to determine the relationship between students' knowledge of the observance of healthy snacks consumption behavior in sdn 03 source salak ledokombo jember, This type of research is a quantitative descriptive research, the sample in this study is students with a total of 40 students. Two variables, namely the relationship between students' knowledge of the observance of healthy snack consumption behavior in sdn 03 source salak ledokombo jember, the instrument used is using a questionnaire, based on table 4.6, the results obtained are categorized as good (22.8%) as many as 29 students, categorized as moderate (7.2%) as many as 11 students and categorized as less none. Based on the results of research that has been conducted by researchers regarding the relationship between students' knowledge of eating healthy snacks, it can be concluded as follows: the relationship between students' knowledge of eating healthy snacks is categorized as good there are 29 students (22.8%) and categorized as moderate as 11 students (7.2%).